Molecular mechanisms after optic nerve injury: Neurorepair strategies from a transcriptomic perspective - Xiaxue Chen; Muyang Wei; Guangyu Li (Neural Regeneration Research)
Retinal ganglion cells, a crucial component of the central nervous system, are often affected by irreversible visual impairment due to various conditions, including trauma, tumors, ischemia, and glaucoma. Studies have shown that the optic nerve crush model and glaucoma model are commonly used to study retinal ganglion cell injury. While these models differ in their mechanisms, both ultimately result in retinal ganglion cell injury. With advancements in high-throughput technologies, techniques such as microarray analysis, RNA sequencing, and single-cell RNA sequencing have been widely applied to characterize the transcriptomic profiles of retinal ganglion cell injury, revealing underlying molecular mechanisms. This review focuses on optic nerve crush and glaucoma models, elucidating the mechanisms of optic nerve injury and neuron degeneration induced by glaucoma through single-cell transcriptomics, transcriptome analysis, and chip analysis. Research using the optic nerve crush model has shown that different retinal ganglion cell subtypes exhibit varying survival and regenerative capacities following injury. Single-cell RNA sequencing has identified multiple genes associated with retinal ganglion cell protection and regeneration, such as Gal, Ucn, and Anxa2. In glaucoma models, high-throughput sequencing has revealed transcriptomic changes in retinal ganglion cells under elevated intraocular pressure, identifying genes related to immune response, oxidative stress, and apoptosis. These genes are significantly upregulated early after optic nerve injury and may play key roles in neuroprotection and axon regeneration. Additionally, CRISPR-Cas9 screening and ATAC-seq analysis have identified key transcription factors that regulate retinal ganglion cell survival and axon regeneration, offering new potential targets for neurorepair strategies in glaucoma. In summary, single-cell transcriptomic technologies provide unprecedented insights into the molecular mechanisms underlying optic nerve injury, aiding in the identification of novel therapeutic targets. Future researchers should integrate advanced single-cell sequencing with multi-omics approaches to investigate cell-specific responses in retinal ganglion cell injury and regeneration. Furthermore, computational models and systems biology methods could help predict molecular pathways interactions, providing valuable guidance for clinical research on optic nerve regeneration and repair.